Association of muscular fitness and body fatness with cardiometabolic risk factors: The FUPRECOL study (2018)
This study investigated the associations of muscular fitness and various indicators of body fatness with cardio-metabolic risk factors and determined the muscular strength and body fatness thresholds for detecting a high risk of cardio-metabolic dysfunction in young adults. A cross-sectional study was conducted on 1798 collegiate students (61.5% females, mean age 20.5 years). Muscular fitness was determined by using a handgrip strength test and normalized grip strength (NGS = handgrip (kg)/body mass (kg)). Body mass index (BMI), waist circumference (WC), percentage of fat mass (BF%), fat-mass index (FMI), and waist-to-height ratio (WHR) were also included as body fatness measurements. A high cardio-metabolic risk cluster was derived by assessing triglycerides, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, fasting glucose, and blood pressure. Logistic regression models showed that men and women with lower NGS had an increased cardio-metabolic risk odds ratio (OR) = 1.8, 95% confidence interval (CI) 1.1 to 2.9, p = 0.006, and OR = 1.6, 95% CI 1.0 to 2.5, p = 0.036, respectively). In both sexes, higher levels of all fatness parameters were also associated with increased cardio-metabolic risk (p less than 0.001). In both men and women, high FMI had the highest OR for clustered risk (OR = 4.7, 95% CI 2.6 to 8.4, and OR = 7.3, 95% CI 3.4 to 9.7, p less than 0.001, respectively). Combined analysis showed that unfitness (lower NGS) and high fat had the highest OR for WC and FMI in men and women, respectively (OR = 5.5, 95% CI 2.6 to 11.4, OR = 7.7, 95% CI 2.3 to 15.8, p less than 0.01). Muscular strength and body fatness are independently and jointly associated with increased cardiometabolic risk in young adults, which suggests that both are predictor variables for this. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.